Vladivostok Railway Station: Designs and reconstruction of the early 20th century - Bazilevich, Mikhail; Glatolenkova, Ekaterina (project baikal, 2023)
The article is devoted to architectural and planning peculiarities of the Vladivostok Railway Station. It analyses previously unpublished design drawings of the first building made by architect P. E. Bazilevsky and reconstruction drawings of the early 20th century made by V. A. Planson with participation of F. E. Niklevich and N. V. Konovalov.
Keywords: Vladivostok; railway station; railway architecture; V. A. Planson; reconstruction